Ultrastructural Localization of Polygalacturonase in Ethylene-Stimulated Abscission of Tomato Pedicel Explants - Ming-Fang Qi; Tao Xu; Wei-Zhi Chen; Tian-lai Li (The Scientific World Journal)
Polygalacturonase (PG) is crucial in plant organ abscission process. This paper investigated the cellular and subcellular localization of PG in ethylene-stimulated abscission of tomato pedicel explants. Confocal laser scanning microscopy of abscission zone sections with the fluorescent probe Cy3 revealed that PG was initially accumulated in parenchyma cells in cortical and vascular tissues after 8 h of ethylene treatment and then extended throughout the abscission zone when the abscission zone separated at 24 h after ethylene treatment. At the subcellular level, transmission electron microscopy with immunogold staining showed that PG showed abundant accumulation in the cortical and vascular tissues at 8 h after ethylene treatment, and the distribution area extended to the central parenchyma cells at 16 h after ethylene treatment. In addition, PGs were observed in the distal and proximal parts of the tomato pedicel explants throughout the abscission process. The results provided a visualized distribution of PG in the pedicel abscission zone and proved that PG was closely related to abscission.